cis,cis-Germacranolides and melampolides from Mikania thapsoides - Catalan, Cesar Atilio Nazareno (2003)
The aerial parts of Mikania thapsoides afforded six new cis,cis-germacranolide-type sesquitepene lactones (1-6), of which three (1-3) have an unusual 3,4-epoxy function, and also afforded two new melampolides (7 and 8). All compounds have a trans C-8 lactone ring closure. Their structures were elucidated using 1D and 2D NMR measurements, and the absolute configuration of 1 was determined using the Mosher ester method.